VD_FINDINFO HC / 2014 / 745 vom 8. September 2014 - VD Tribunal cantonal (2014)
RESTITUTION DU DÉLAI, DROIT D'ÊTRE PRÉSENT À L'AUDIENCE, DÉCISION D'IRRECEVABILITÉ | 135 CPC (CH), 148 CPC (CH), 149 CPC (CH)